Behavioral responses of benthic and nektonic tadpoles to the presence of a benthic predator - de Souza, Yasmim Caroline Mossioli [UNESP]; Annibale, Fabiane Santana; Pelinson, Rodolfo Mei [UNESP]; Rossa-Feres, Denise de Cerqueira [UNESP] (Springer Nature, 2024)
We experimentally tested whether the presence of a free benthic predator (Odonata naiads) alters the displacement time, the position occupied in the water column, and the proportion of food consumed by benthic and nektonic tadpoles. The presence of predators did not influence the displacement time or the proportion of food consumed by any of the two species. In the presence of predators, benthic tadpoles avoided the benthic microhabitat, increasing their time in the middle of the water column. This behavior was unexpected since the previous studies indicate that the morphology of benthic tadpoles restricts them to the bottom of water bodies. We, thus, hypothesize that such a drastic behavior change was a consequence of the real risk of predation to which the tadpoles were exposed. Our results are in accordance with the threat-sensitivity hypothesis, in which prey behave flexibly when exposed to different degrees of predation threats. Nektonic tadpoles, however, slightly increased their permanence in the water column in the presence of the same benthic predators. Therefore, we provide support for the hypothesis that predators induce greater behavioral changes in prey that exhibit patterns of microhabitat use similar to theirs.
Keywords: Feeding behavior; Indirect interactions; Induced defense; Occupied depth; Trade-off